The Role of Religiosity, Halal Awareness, Halal Certification, and Food Ingredients on Purchase Intention of Halal Food - Lu’liyatul Mutmainah (Universitas Ahmad Dahlan, 2018)
Halal becomes the lifestyle of Muslim consumers in the world. As the Muslim population increasing, the awareness on consuming halal food also improving. This paper aims to examine the influence of religiosity, halal awareness, halal certification, and food ingredients on purchase intention of halal food among Indonesian Muslim consumers. Convenience sampling was used as the sampling method of this study. This research consisted of 205 respondents. The data are collected by questionnaire which are analyzed by multiple linear regression. The results of this study revealed that religiosity, halal awareness, halal certification and food ingredients have significantly positive effect on purchase intention of halal Food. This study indicates that consuming halal food is primary need for Muslim. Therefore, company should acquire halal certification in order to provide halal food for Muslim’s needs. This study contributed for the research literature, government, food manufacturers and marketers to develop strategies related with halal food.